Transformation of acute kidney injury to chronic kidney disease: the interaction between mitophagy and NLRP3 inflammasome - Zhu, Yixin; Lv, Chenxi; Qiao, Yanheng; Yang, Hanqi; Lin, Wentong; Wang, Xuchen; Zhang, Yueqi; Yang, Bo (Frontiers in Molecular Biosciences, 2025)
Acute kidney injury (AKI) and chronic kidney disease (CKD) are closely interrelated renal disorders, where AKI frequently progresses to CKD, resulting in irreversible loss of renal function. In recent years, the roles of the NLRP3 inflammasome and mitophagy in the AKI-to-CKD transition have attracted significant attention. As a crucial component of the innate immune system, the NLRP3 inflammasome promotes AKI-to-CKD progression by mediating inflammatory responses and cellular pyroptosis during renal injury. Conversely, mitophagy exerts renoprotective effects through the selective removal of damaged mitochondria, maintenance of cellular homeostasis, and alleviation of inflammation and oxidative stress. Studies demonstrate that NLRP3 activation is closely associated with mitochondrial dysfunction, while mitophagy can suppress NLRP3 activation by clearing damaged mitochondria, establishing a negative feedback regulatory mechanism. During the AKI phase, mitochondrial damage and excessive NLRP3 activation exacerbate renal tubular epithelial cell injury and inflammatory responses. Concurrently, persistent NLRP3 activation and impaired mitophagy lead to chronic inflammation and fibrosis, accelerating the transition from AKI to CKD. Therefore, targeting the NLRP3 inflammasome and modulating mitophagy may emerge as novel therapeutic strategies for AKI-to-CKD transition. This review focuses on elucidating the molecular mechanisms between mitophagy and the NLRP3 inflammasome, along with related targeted therapies, to provide new insights for preventing AKI progression to CKD.